Structural biology of SARS-CoV-2 endoribonuclease NendoU (nsp15). Issue 1 (2nd January 2022) - Horrell, Sam; Santoni, Gianluca; Thorn, Andrea
Abstract : The SARS-CoV-2's endoribonuclease (NendoU) nsp15, is an Mn 2+ dependent endoribonuclease specific to uridylate that SARS-CoV-2 uses to avoid the innate immune response by managing the stray RNA generated during replication. As of the writing of this review 20 structures of SARS-CoV-2 nsp15 have been deposited into the PDB, largely solved using X-ray crystallography and some through Cryo-EM. These structures show that an nsp15 monomer consist of three conserved domains, the N-terminal oligomerization domain, the middle domain, and the catalytic NendoU domain. Enzymatically active nsp15 forms a hexamer through a dimer of trimers (point group 32), whose assembly is facilitated by the oligomerization domain. This review summarises the structural and functional information gained from SARs-CoV-2, SARs-CoV and MERS-CoV nsp15 structures, compiles the current structure-based drug design efforts, and complementary knowledge with a view to provide a clear starting point for downstream structure users interested in studying nsp15 as a novel drug target to treat COVID-19.